Design junctions in real-world laboratories. Analyzing Experiences Gained from the Project Knowledge Dialogue Northern Black Forest. - Pregernig, Michael; Rhodius, Regina; Winkel, Georg (Oekom, 2018)
Real-world laboratories (RwLs) stand for a new format of transformative research. Drawing on the concept of "design junctions", we shed light on what is going on inside an RwL. Based on the example of the RwL Knowledge Dialogue Northern Black Forest, we focus on both the negotiation processes over the normative and methodological requirements of RwL research formats as well as the common practices of day-to-day research work. Real-world laboratories (RwLs) promise to advance, and at the same time study, transitions to sustainability in a specific socio-spatial context. That brings challenges for researchers working in RwLs. In this Design Report, we reflect on the experiences researchers have gained in the RwL Knowledge Dialogue Northern Black Forest, Germany. We propose the concept of "design junctions" as deliberate intervention points in the procedural setup of RwLs that are, however, still contingent on the normative and methodological expectations of this special type of research. We present five design junctions tied to the questions of how to position an RwL in a politicized environment, deploy an interdisciplinary research team, develop the research program in a participatory way, incentivize transdisciplinarity, and engage with stakeholders and citizens.
Keywords: Nachhaltige Entwicklung; Nationalpark; Regionalentwicklung; Wissenstransfer; Reallabor; Fallbeispiel